2013
DOI: 10.3109/10717544.2013.848246
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of curcumin delivery with functionalized single-walled carbon nanotubes: characteristics and anticancer effectsin vitro

Abstract: Context: Single-walled carbon nanotubes (SWCNTs), an important class of artificial nanomaterials with unique physicochemical properties, were used as novel carriers of curcumin. Objective: Formulation and evaluation of curcumin-loaded SWCNTs systems for utilizing the curcumin's anticancer potential by circumventing conventional limitations of extremely low aqueous solubility and instability under physiological conditions, and combining SWCNTs photothermal therapy enabled by the strong optical absorbance of SWC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 30 publications
0
41
0
Order By: Relevance
“…Owing to their high surface area ratio, MWCNTs have strong loading capacity for a variety of agents including biomolecules (proteins or nucleic acids) and chemical drugs (either hydrophilic or hydrophobic) (Li et al, 2014;Qi et al, 2015). They can also increase the bioavailability of these molecules by controlling their release or protecting them from degradation or alleviate their toxicity and harmful side effects through targeted delivery (Mu et al, 2009;Li et al, 2016;Mehra & Palakurthi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their high surface area ratio, MWCNTs have strong loading capacity for a variety of agents including biomolecules (proteins or nucleic acids) and chemical drugs (either hydrophilic or hydrophobic) (Li et al, 2014;Qi et al, 2015). They can also increase the bioavailability of these molecules by controlling their release or protecting them from degradation or alleviate their toxicity and harmful side effects through targeted delivery (Mu et al, 2009;Li et al, 2016;Mehra & Palakurthi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…After carefully optimizing these physicochemical parameters, CNT can be used in biomedical applications as biocompatible materials (Lanone et al, 2013). In this study, according to a method reported previously (Li et al, 2013;Wang et al, 2013), pristine SWNT were first treated with acids (H 2 SO 4 and HNO 3 ) and sonication to remove metal contaminants, shorten the length and oxidize the ends to reduce the aggregation. Furthermore, carboxyl groups in oxidated SWNT allow for the possibility of combining with a cation to form a salt, thereby enhancing the solubility of SWNT.…”
Section: Characteristics Of Swnt-dotapmentioning
confidence: 99%
“…According to the method reported previously by our group (Li et al, 2013), SWNT were processed with acids (H 2 SO 4 and HNO 3 ) and ultrasound to obtain purified, shortened and oxidized SWNT. Oxidized SWNT were used unless stated otherwise.…”
Section: Purification Cutting and Oxidation Of Swntmentioning
confidence: 99%
See 1 more Smart Citation
“…226,239,240 Recently, curcumin was conjugated to a single wall carbon nanotube for the effective delivery. 241 The role of hyaluronic acids in the delivery of drugs using carbon nanotubes was reviewed recently, 242 and further clinical trials are needed to assess their biosafety. However, a study on the application of carbon nanotubes with phytocompounds in skin care and cosmeceuticals is yet to be done.…”
mentioning
confidence: 99%